Penerapan Layanan E-health pada Puskesmas Kota Surabaya dalam Memberikan Pelayanan kepada Masyarakat: Literature Review - Rusbaya, Ageng; Ernawaty, Ernawaty (Universitas Faletehan, 2024)
Globalization brought changes to traditional governance from paper-based administration to electronic governance services (e-government). The Surabaya City Government through the implementation of e-government formed e-health services to improve health services. The purpose of this study was to analyze the application of e-health services in health services at the Surabaya City Health Centers. The method of this research used a literature review study. The Publish on Perish application was used in Google Scholar searches with the keywords